The research of coal seam gas pressure and initial gas emission characteristics of borehole - Jianhua Zeng; Shixiang Tian; Guiyi Wu; Yunjun Zuo; Shiqing Xu; Peng Pei; Chen Wang (Energy Science & Engineering, 2019)
Abstract Gas pressure is one of the major factors to characterize the outburst danger of coal seams. Generally, the process of gas pressure determination is complicate and cannot ensure the accuracy of results, which may cause a wrong identification of outburst danger. This paper discussed and revealed a positive correlation between initial gas emission and gas pressure, which provides a new approach to identify the outburst danger by initial gas emission. Through theoretical analysis and numerical simulation, the liner equation of gas pressure and initial gas emission was deduced. Laboratory experiments under adsorption and desorption of CO2 and N2 were performed using coal samples from Weishe coal mine. The data of initial gas emission under different gas pressure were recorded, and the fitting curves were obtained. The results show a positive correlation between initial gas emission and gas pressure, and the curve of N2 was below the CO2. Especially, while the adsorption gas pressure was under 0.663 and 0.675 MPa, the difference of corresponding initial gas emission was only 0.01 L/s, which indicates the high degree of correlation. The results validated the theoretical and practical feasibility to identify the coal and the gas outbursts through initial gas emission.